Probabilistic Linguistic Grey Target Group Decision-Making Method Considering Decision Makers’ Expected Information - Peng Li; Chen Zhu (Systems, 2025)
Grey target decision making is a useful tool to solve multiple-criteria decision-making problems. Decision makers’ expected information can reflect their preferences and play an important role in decision process. In this paper, a new grey target group decision-making method considering decision makers’ expected information is proposed. First, based on the decision makers’ expected information, a novel method to obtain synthetical criteria weights combining subjective weights and objective weights is presented. Furthermore, a new way to determine decision makers’ weights is put forward. Moreover, on the basis of the decision matrix, criteria weights, and decision makers’ weights, a ranking method for all alternatives is proposed. Finally, a case for maintaining a precise instrument in a nursing home is used to illustrate the effectiveness of our proposed method.